2010
DOI: 10.1111/j.1439-0396.2008.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cellulose fibre length on faecal quality, mineral excretion and nutrient digestibility in cat

Abstract: In dogs, faeces quality and nutrients digestibility were affected by different types of cellulose (Wichert et al., 2002). In this study, it was investigated whether there are comparable effects of cellulose type in cats. Seven adult, healthy cats were fed a moist commercial complete cat food with three different cellulose type added at a level of 4% for a 1 week period. Faeces quality was between 1 and 3 on the scale used from 1 to 5. The addition of long fibre cellulose resulted in significantly firmer faeces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…Prola et al. (), in agreement with earlier studies by Kienzle (), found that in adult cats fed diets for 1 week with different cellulose types added at a level of 4%, faecal excretion of sodium was exponentially correlated with faecal water ( R 2 = 0.81), faecal bulk ( R 2 = 0.77) and (to a lesser extent) faecal dry matter excretion ( R 2 = 0.55).…”
Section: Sodium Balance and Dietary Requirementssupporting
confidence: 80%
See 1 more Smart Citation
“…Prola et al. (), in agreement with earlier studies by Kienzle (), found that in adult cats fed diets for 1 week with different cellulose types added at a level of 4%, faecal excretion of sodium was exponentially correlated with faecal water ( R 2 = 0.81), faecal bulk ( R 2 = 0.77) and (to a lesser extent) faecal dry matter excretion ( R 2 = 0.55).…”
Section: Sodium Balance and Dietary Requirementssupporting
confidence: 80%
“…Dietary factors include those related to faecal bulk and water content. Largely fermentable fibre sources increase the water content of faeces, and the type and inclusion level of non‐fermentable fibre increase faecal bulk, leading to increased faecal sodium excretion (Kienzle, ; Prola et al., ). On the other hand, few studies have investigated factors that affect sodium absorption in cats.…”
Section: Sodium Balance and Dietary Requirementsmentioning
confidence: 99%
“…The effects of dietary fiber on stool quality may be related to the length of cellulose fiber rather than the absolute amount of fiber [18]. Similarly, in cats the addition of dietary fiber in the form of long-fiber cellulose enhances stool quality [19]. Thus, not only the amount of fiber delivered to the large bowel, but also the type of fiber is important for stool quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that an overabundance of protein in the diet may be a negative factor for stool quality, whereas dietary fiber is a positive factor [16][19]. These findings assume that excess protein or dietary fiber is passed into the large intestine providing substrate for microbial fermentation and growth.…”
Section: Introductionmentioning
confidence: 97%
“…Both studies used a similar inclusion level of the dietary fibre sources. Likewise, the inclusion of cellulose at a high level (17 % DM) did not alter food intake in cats (78,79) and the addition of psyllium husks and seeds did not decrease diet acceptance in cats with constipation (8) .…”
Section: In Vivo Studiesmentioning
confidence: 97%